2012
DOI: 10.1242/dev.083410
|View full text |Cite
|
Sign up to set email alerts
|

Tup/Islet1 integrates time and position to specify muscle identity in Drosophila

Abstract: SUMMARYThe LIM-homeodomain transcription factor Tailup/Islet1 (Tup) is a key component of cardiogenesis in Drosophila and vertebrates. We report here an additional major role for Drosophila Tup in specifying dorsal muscles. Tup is expressed in the four dorsal muscle progenitors (PCs) and tup-null embryos display a severely disorganized dorsal musculature, including a transformation of the dorsal DA2 into dorsolateral DA3 muscle. This transformation is reciprocal to the DA3 to DA2 transformation observed in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 68 publications
(104 reference statements)
2
49
0
Order By: Relevance
“…Tup is also expressed in AMs, in addition to the heart and the dorsal DA1, DA2, DO1 and DO2 muscles (Tao et al, 2007;Boukhatmi et al, 2012), dorsal ectoderm, amnioserosa and precursor cells of the pharynx (Thor and Thomas, 1997;Ashe et al, 2000). Expression of the org-1-HN39-lacZ (org-1-lacZ) reporter recapitulates org-1 expression in the somatic musculature (Schaub et al, 2012), while both IsletH-GFP and tupF4-GFP, two overlapping reporter constructs, reproduce tup expression in AMs (Tao et al, 2007;Boukhatmi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tup is also expressed in AMs, in addition to the heart and the dorsal DA1, DA2, DO1 and DO2 muscles (Tao et al, 2007;Boukhatmi et al, 2012), dorsal ectoderm, amnioserosa and precursor cells of the pharynx (Thor and Thomas, 1997;Ashe et al, 2000). Expression of the org-1-HN39-lacZ (org-1-lacZ) reporter recapitulates org-1 expression in the somatic musculature (Schaub et al, 2012), while both IsletH-GFP and tupF4-GFP, two overlapping reporter constructs, reproduce tup expression in AMs (Tao et al, 2007;Boukhatmi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Staining embryos at that stage for Tup and rp298(duf)-lacZ, a marker of muscle PCs and FCs (Nose et al, 1998), identified the four PCs at the origin of the DA1, DO2, DO1 and DA2 dorsal muscles, plus another cell located several cell diameters posterior to the DA2/AMP PC (Boukhatmi et al, 2012). Double staining for Org-1 and IsletH-GFP shows that this cell is the AM progenitor and is segmentally repeated along the posterior/anterior segmental border ( Fig.…”
Section: Am and Tarm Lineage Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…FCs dictate the number of cell fusion events that take place, leading to a characteristic number of nuclei for each muscle in the pattern . These fusing nuclei adopt the transcriptional profile of the original FC nucleus (Bourgouin et al 1992;D'Alessio and Frasch 1996;Ruiz-Gomez et al 1997;Jagla et al 1998;Keller et al 1998;Nose et al 1998;Crozatier and Vincent 1999;Knirr et al 1999;Duan et al 2007;Muller et al 2010;Carrasco-Rando et al 2011;Boukhatmi et al 2012;Schaub et al 2012), which determines the specific morphological features of each muscle fiber.The identity of each FC, and its capacity to confer this identify on the resulting muscle fiber, is determined by expression of a unique combination of transcription factors in FCs (Baylies et al 1998;Frasch 1999;Beckett and Baylies 2007;Tixier et al 2010). Correspondingly, the loss or misexpression of these identity transcription factors (iTFs) can affect the formation and morphology of the specific muscles in which they are expressed.…”
mentioning
confidence: 99%
“…FCs dictate the number of cell fusion events that take place, leading to a characteristic number of nuclei for each muscle in the pattern . These fusing nuclei adopt the transcriptional profile of the original FC nucleus (Bourgouin et al 1992;D'Alessio and Frasch 1996;Ruiz-Gomez et al 1997;Jagla et al 1998;Keller et al 1998;Nose et al 1998;Crozatier and Vincent 1999;Knirr et al 1999;Duan et al 2007;Muller et al 2010;Carrasco-Rando et al 2011;Boukhatmi et al 2012;Schaub et al 2012), which determines the specific morphological features of each muscle fiber.…”
mentioning
confidence: 99%